1980
DOI: 10.1007/bf00432862
|View full text |Cite
|
Sign up to set email alerts
|

Results of alloarthroplasty of the hip joint

Abstract: We report on the follow-up examination results of 881 operated hip joints which were implanted in the Innsbruck University Clinic for Orthopedics during the period 1968--1975. Due to exact checking 75% of all patients could be clinically control-examined during 1978 and all available information regarding the others was collected. In the patient group with an average age of 62.5 years the course of postoperative mobility over the years was mainly examined. Functional activity, subjective patient opinion, pain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A total of more than 400 study reports were reviewed. From these reports, 218 studies were confirmed as eligible 9,10,13,15−226 and the remainder were excluded. The principal reasons for the exclusion of studies were the absence of information about the incidence of heterotopic bone formation or about the number of participants or hips, 7,14 , 227−279 the conduct of other surgical procedures (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A total of more than 400 study reports were reviewed. From these reports, 218 studies were confirmed as eligible 9,10,13,15−226 and the remainder were excluded. The principal reasons for the exclusion of studies were the absence of information about the incidence of heterotopic bone formation or about the number of participants or hips, 7,14 , 227−279 the conduct of other surgical procedures (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The figure for heterotopic ossification of 17.6% obtained in the present study falls roughly within the average range. There is less divergence in cases of severe ossification with clinically relevant limitation of movement; here the figures range from 1.2% to 7% [16,19], and are often around 4% [2,8]. Our own figure for severe heterotopic ossification of 2.3% is at the lower end of this range.…”
Section: Discussionmentioning
confidence: 86%